Рефлекс змеи: [роман] : (16+) / Дик Фрэнсис ; [перевод с английского Н. Некрасовой] - Фрэнсис Дик (Весь Фрэнсис, 2014)
Экземпляры: аб (20151218) / Инвентарный номер: 060101 / Цена: 116.00 / Авт.знак: Ф 93 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)